Đồng nhất hoá các đường đặc tính uốn của cánh quay trực thăng dựa theo kết quả của phương pháp kiểm thử tần số - Sơn, Lê Thế (Journal of Computer Science and Cybernetics, 2016)
The certification of the controlled model of helicopter usually concerns necessity to certificate elastic characteristics of helicopter's rotor blade. The use of data from experiment usually raises certain significant errors, therefore the use of data from the frequency test plays a role more appropriate, especially, in the identification of elastic characteristics of helicopter's rotor blade. In this paper, we wish present a solution for the problem by identifying the forms of experiment natural oscillation and the forms of theoretical natural oscillation. The selected criteria are general criteria that are equivalentc to the sum of separated criteria; each criterion is sum of square error, which received from equations natural oscillation of the rotor blade. In other words, the resolution problem of the Identification of elastic characteristics of rotor blade is brought to the resolution problem of extreme value and the determination of minimum function I (14). By this way, it allows us to get more accurate elastic characteristics of the rotor blade.